Inorganic Fe-O and Fe-S oxidoreductases: paradigms for prebiotic chemistry and the evolution of enzymatic activity in biology - Huang, Xiao-Lan; Harmer, Jeffrey R.; Schenk, Gerhard; Southam, Gordon (Frontiers in Chemistry, 2024)
Oxidoreductases play crucial roles in electron transfer during biological redox reactions. These reactions are not exclusive to protein-based biocatalysts; nano-size (<100 nm), fine-grained inorganic colloids, such as iron oxides and sulfides, also participate. These nanocolloids exhibit intrinsic redox activity and possess direct electron transfer capacities comparable to their biological counterparts. The unique metal ion architecture of these nanocolloids, including electron configurations, coordination environment, electron conductivity, and the ability to promote spontaneous electron hopping, contributes to their transfer capabilities. Nano-size inorganic colloids are believed to be among the earliest 'oxidoreductases' to have 'evolved' on early Earth, playing critical roles in biological systems. Representing a distinct type of biocatalysts alongside metalloproteins, these nanoparticles offer an early alternative to protein-based oxidoreductase activity. While the roles of inorganic nano-sized catalysts in current Earth ecosystems are intuitively significant, they remain poorly understood and underestimated. Their contribution to chemical reactions and biogeochemical cycles likely helped shape and maintain the balance of our planet's ecosystems. However, their potential applications in biomedical, agricultural, and environmental protection sectors have not been fully explored or exploited. This review examines the structure, properties, and mechanisms of such catalysts from a material’s evolutionary standpoint, aiming to raise awareness of their potential to provide innovative solutions to some of Earth’s sustainability challenges.